Intimal Hemorrhage of Basilar Artery Induced by Severe Vasospasm Following Subarachnoid Hemorrhage: The Experimental Analysis - Gökyar, Ahmet; Şahin, Mehmet Hakan; Karadağ, Mehmet Kürşat; Bahadır, Sinan; Zeynal, Mete; Sipal, Sare Altas; Aydin, Mehmet D. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2024)
Background Cerebral vasospasm, a serious complication of subarachnoid hemorrhage (SAH), has been extensively studied for its neurochemical and pathophysiologic mechanisms. However, the contribution of inner elastic membrane dissection and subintimal hemorrhage to basilar artery occlusion remains underexplored. This study investigates inner elastic membrane-related changes in the basilar artery after SAH.Methods Twenty-four hybrid rabbits were divided into control, sham, and SAH groups, with SAH induced by autologous blood injection. After 2 weeks, basilar artery changes, vasospasm indexes (VSIs), and dissections were evaluated.Results The SAH group showed significantly higher VSI, with vascular wall thickening, luminal narrowing, convoluted smooth muscle cells, intimal elastic membrane disruption, endothelial cell desquamation, and apoptosis. Some SAH animals exhibited subintimal hemorrhage, inner elastic membrane dissection, and ruptures. Basilar arteries with subintimal hemorrhage had notably higher VSI.Conclusions These findings highlight the role of subintimal hemorrhage and inner elastic membrane dissection in basilar artery occlusion post-SAH, offering valuable insights into vasospasm pathophysiology.
Keywords: subarachnoid hemorrhage; basilar artery; inner elastic membrane; subintimal hemorrhage; stereological analysis